Upregulation of microRNA miR-141-3p and its prospective targets in endometrial carcinoma: a comprehensive study. Issue 1 (1st January 2021) - Yang, Lin-Jie; Gao, Li; Guo, Yi-Nan; Liang, Zi-Qian; Li, Dong-Ming; Tang, Yu-Lu; Liu, Yi-Hong; Gao, Wan-Jing; Zeng, Jing-Jing; Shi, Lin; Wei, Kang-Lai; Chen, Gang
ABSTRACT: The clinicopathological value of microRNA-141-3p (miR-141-3p) and its prospective target genes in endometrial carcinoma (EC) remains unclear. The present study determined the expression level of miR-141-3p in EC via quantitative real-time PCR (RT-qPCR). RT-qPCR showed a markedly higher expression level of miR-141-3p in EC tissues than in non-EC endometrium tissues ( P < 0.0001). The microarray and miRNA-seq data revealed upregulation of miR-141-3p. Integrated analysis based on 675 cases of EC and 63 controls gave a standardized mean difference of 1.737, confirmed the upregulation of miR-141-3p. The Kaplan-Meier survival curve showed that a higher expression of miR-141-3p positively corelated with a poorer prognosis. Combining the predicted targets and downregulated genes in EC, we obtained 271 target genes for miR-141-3p in EC. Two potential targets, PPP1R12A and PPP1R12B, were downregulated at both the mRNA and protein levels. This study indicates that the overexpression of miR-141-3p may play an important part in the carcinogenesis of EC. The overexpression of miR-141-3p may be a risk factor for the prognosis of patients with EC. Graphical Abstract: uf0001